Digital profile of journalists in Ecuador: Study of digital version of six national general newspapers [Perfil de los periodistas digitales en Ecuador: Estudio de seis diarios nacionales de información general en su versión digital] - Gonzales Cordova, M. (2017)
This research is about the journalist profile in Ecuador, his role, characteristics, education, knowledge, content management, and use of ICTs in his daily job. To fulfill this purpose, 6 national newspapers in their digital version have been studied: El Universo, El Comercio, La Hora (National and Regional), El Telégrafo, Expreso and Extra. This is a qualitative and quantitative research, the techniques used to gather data was the structured questionnaire. © 2016, Universidad del Zulia. All rights reserved.